Dynamic Response and Parametric Studies of Elliptical Blast-Resistant Door with the Combined Structure for Large Vacuum Explosion Containers. (3rd November 2021) - Cheng, Saiwei; Li, Xiaojie; Wang, Yang; Wang, Yuxin; Yan, Honghao
Abstract : In recent years, with the improvement of environmental protection requirements year by year and the continuous expansion of explosive working scale, higher standards have been put forward for explosive working. It is hoped that the sphere of influence of the explosion can be limited to a minimal range. The explosion vessel is driven by such demand. As the explosion vessel's key component, studying the blast-resistant door in depth is of great significance. This paper introduces a new elliptical blast-resistant door with the combined structure (EBD), mainly welded with an elliptical panel, arc support plate, and triangle support plate. The finite element program AUTODYN was used to calculate the explosion load, and LS-DYNA was used to calculate the blast-resistant door's dynamic response. The calculation results show that the newly proposed EBD's blast-resistance capacity is better than that of the traditional structure. To further study the factors that affect the dynamic response of the EBD, a parametric study was carried out on the EBD, mainly analyzing the influence of the vacuum degree in the explosion vessel, the number of explosives, and the diameter ratio of the EBD. The parametric calculation results show that reducing the vacuum degree in the explosion vessel and the number of explosives during explosion working can improve the blast-resistance capacity of the EBD. Based on the analysis of the dynamic response of four kinds of EBD with different diameter ratios under 0.2 atm explosion load, the optimal diameter ratio of the EBD is given.